Pengaruh Penerapan Metode Demonstrasi Terhadap Hasil Belajar Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas VIII SMP Negeri 1 Sipoholon - Feni Yolanda Br. Sianturi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The aim of this research is to determine the effect of applying the demonstration method on the learning outcomes of Christian Religious Education & Character Education in class VIII of SMP Negeri 1 Sipoholon for the 2023/2024 academic year.This research uses a Posttest-Only Control type experimental method. The population is the entire class VIII of SMP Negeri 1 Sipoholon for the 2023/2024 academic year, totaling 160 people. The sample was determined using a technique taken deliberately (purposive sampling) with the specified conditions that the learning material being experimented with was in that class, namely 32 students in class VIII-C as the experimental class and 32 students in VIII-E as the control class. The research instrument used a 27 item test. The t test used is the Separated Variance t test according to the test analysis requirements, namely n1=n2 and the variance of the two sample groups is homogeneous. The results of hypothesis testing obtained a value of tcount= 13.9 > ttable (a=0.05; dk=n1+n2-2=62) = ttable 1.669, so H0 is rejected and H1 is accepted. This research concludes that the learning outcomes of students' Christian Religion & Character Education taught using the demonstration method are higher than those taught using the lecture method in class VIII of SMP Negeri 1 Sipoholon for the 2023/2024 Academic Year. Keywords: Demonstration Method, Learning Outcomes